Reduction of Religion: Attitude and Religious Behavior of Indonesian College Students - M. Hanafiah; Nadiyah; Lutfi, Lutfi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2023)
This research is motivated by the phenomenon of strengthening radicalism in the campus involving students and lecturers. The findings of several studies confirm an increasing trend of radicalism among students. The purpose of this research is to answer the main issue of the research which is to find out radicalism among public and religious college students. This research is field research, data and information obtained directly in the field, using quantitative methods. Data collection techniques through a closed questionnaire (closed questionnaire) using a Likert Scale. A number of universities in Java and Kalimantan were sampled in this study. This research found that radicalism among public and religious college students fluctuated with narrative responses at the level of soft radicalism. However, the narrative of radicalism is so strong in understanding, but tends to show a downward trend in attitudes and behavior. The idea of ​​applying Islamic law is still the main choice for most respondents, but it is inversely related to the response to the application of the caliphate. Prohibition of Hizbut Tahrir Indonesia (HTI) organization is effective in reducing the attitude and behavior of radicalism among students.